¿Where do migratory fish spawn in a neotropical Andean basin regulated by dams? - Kelly Rivera-Coley; David Augusto Reynalte-Tataje; Víctor Atencio-Garcia; Omer Campo; Luz Jímenez-Segura (PLoS ONE, 2023)
Spawning sites play a key role in the reproduction of fish allowing populations to endure over time. The Nechí River is an important spawning area for potamodromous fish species where one of the threats is dam construction. In order to determine the importance of the Nechí River as a spawning site in the Magdalena River basin, sampling was conducted during the low-water-to-high-water season transition period between 2018 and 2019 at seven sampling sites. The average density of ichthyoplankton was 42.4 ind.10m-3 (SD = 7.1). Of the individuals in the post-larval stage, seven migratory species were identified, and two additional taxa were identified to genus; Prochilodus magdalenae, Megaleporinus muyscorum, and Pseudoplatystoma magdaleniatum presented the greatest density. At the temporal level, the greatest density of larvae of potamodromous species was observed in the first high-water season of 2019 with a total of 5.7 ind.10m-3(SD = 1.044), of which the most representative at the seasonal level were the Cauca River, Magdalena River, and Nechí River before it flows into the Cauca River. There were significant differences in the frequency of embryos and vitelline larvae of the potamodromous species in the interaction of the sampling sites and high-water seasons, as well as with the density of post-larvae. The average drift distance of the spawning areas is roughly 52.1 km. A positive association was found between the volume of turbined water and the presence of ichthyoplankton in the Porce River site, after discharge from the Porce III Hydroelectric Plant. The Nechí River is an important spawning site and there seems to be an association between the increase in ichthyoplankton densities and the distance to the dam (Porce III) as long as there are floodplains along the course of the river.